2015
DOI: 10.1021/acs.accounts.5b00284
|View full text |Cite
|
Sign up to set email alerts
|

Amine–Oxide Hybrid Materials for CO2 Capture from Ambient Air

Abstract: Oxide supports functionalized with amine moieties have been used for decades as catalysts and chromatographic media. Owing to the recognized impact of atmospheric CO2 on global climate change, the study of the use of amine-oxide hybrid materials as CO2 sorbents has exploded in the past decade. While the majority of the work has concerned separation of CO2 from dilute mixtures such as flue gas from coal-fired power plants, it has been recognized by us and others that such supported amine materials are also perh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
249
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 270 publications
(261 citation statements)
references
References 61 publications
3
249
0
9
Order By: Relevance
“…Some of the most studied adsorbents for DAC are solid hybrid adsorbents based on polyamines impregnated or chemically bound on supports including silica, mesoporous solids (SBA‐15, MCM‐41, MCM‐48, etc. ), hyperbranched silicas (HAS), alumina, various polymers, carbon, and carbon fibers . Our group reported, for example, the straightforward and simple preparation and use of both LPEI and BPEI impregnated on precipitated and fumed silica as superior adsorbents for DAC under dry and humid conditions …”
Section: Resultsmentioning
confidence: 99%
“…Some of the most studied adsorbents for DAC are solid hybrid adsorbents based on polyamines impregnated or chemically bound on supports including silica, mesoporous solids (SBA‐15, MCM‐41, MCM‐48, etc. ), hyperbranched silicas (HAS), alumina, various polymers, carbon, and carbon fibers . Our group reported, for example, the straightforward and simple preparation and use of both LPEI and BPEI impregnated on precipitated and fumed silica as superior adsorbents for DAC under dry and humid conditions …”
Section: Resultsmentioning
confidence: 99%
“…This last role is of increasing importance as part of concerted efforts to capture carbon dioxide and lower carbon emissions, and many MOFs have been shown to adsorb CO 2 . In particular, it has been shown that internal functionalization of MOFs with amine groups can result in highly impressive CO 2 uptake and storage …”
Section: Introductionmentioning
confidence: 99%
“…[5] Die Anforderungen an die Reinheit von CO 2 aus der Luft für Sabatier-oder Fischer-Tropsch-Prozesse sind deutlich höher [6,7]. Nichtsdestotrotz sollte berücksichtigt werden, dass die Abtrennung aus der Luft wegen der geringen Konzentration sehr aufwendig ist.…”
Section: Brennstoffeunclassified